2015
DOI: 10.1016/j.biomaterials.2015.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Engineered composite tissue as a bioartificial limb graft

Abstract: The loss of an extremity is a disastrous injury with tremendous impact on a patient’s life. Current mechanical prostheses are technically highly sophisticated, but only partially replace physiologic function and aesthetic appearance. As a biologic alternative, approximately 70 patients have undergone allogeneic hand transplantation to date worldwide. While outcomes are favorable, risks and side effects of transplantation and long-term immunosuppression pose a significant ethical dilemma. An autologous, bio-art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 38 publications
6
107
0
Order By: Relevance
“…The peripheral sensory nerve structure in the flap matrix could easily bridge the host nerve growth into the flap. Indeed, we observed cellularization in the nerve structure after its end-to-side connection with the femoral nerve in the host; however, whether nerve function can fully recover in this setting requires further investigation [12, 51]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peripheral sensory nerve structure in the flap matrix could easily bridge the host nerve growth into the flap. Indeed, we observed cellularization in the nerve structure after its end-to-side connection with the femoral nerve in the host; however, whether nerve function can fully recover in this setting requires further investigation [12, 51]. …”
Section: Discussionmentioning
confidence: 99%
“…More recently, Jank et al created decellularized limb composite tissue matrix. The recellularized limb tissue matrix–multiple cells construct showed perfusion in a re-endothelialized vascular conduit in a short-term non-survival procedure in a rat model [12]. Overall, the use of decellularized composite tissue matrix to engineer vascularized composite tissue has progressed much in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Although perfusion decellularization has been performed on the entire forelimb of a rat 26 and whole organs, such as the liver, 27 heart, 28 kidneys, 29 and lungs, 30 muscle tissue lacks the easily accessible vasculature needed for perfusion, motivating a different approach whereby decellularization solution was infused into the bulk tissue using a needle. In our recently published work, it was demonstrated that DSM scaffolds produced through infusion decellularization retain the composition, mechanics, and architecture of native muscle ECM.…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies reviewed herein also suggest that ECM scaffolds have potential as cell delivery scaffolds, although this significantly increases treatment costs and has a more difficult regulatory pathway as a combination product. More long term development could result in the use of decellularized ECM for whole organ engineering [9295]; however, this increase in complexity creates numerous more challenges that must be overcome, including creating fully functional constructs and preventing thrombosis in the vasculature [96, 97]. …”
Section: Current Challenges and Future Opportunitiesmentioning
confidence: 99%